Rifampin Use and Safety in Hospitalized Infants - Arnold, Christopher J.; Ericson, Jessica; Kohman, Jordan; Corey, Kaitlyn L.; Oh, Morgan; Onabanjo, Janet; Hornik, Christoph P.; Clark, Reese H.; Benjamin, Daniel K., Jr.; Smith, P. Brian; Chu, Vivian H.; on behalf of the Best Pharmaceuticals for Children Act–Pediatric Trials Network Administrative Core Committee (American Journal of Perinatology, 2015)
Objective This study aims to examine the use and safety of rifampin in the hospitalized infants.Study Design Observational study of clinical and laboratory adverse events among infants exposed to rifampin from 348 neonatal intensive care units managed by the Pediatrix Medical Group between 1997 and 2012.Result Overall, 2,500 infants received 4,279 courses of rifampin; mean gestational age was 27 weeks (5th, 95th percentile; 23, 36) and mean birth weight was 1,125 g (515; 2,830). Thrombocytopenia (121/1,000 infant days) and conjugated hyperbilirubinemia (25/1,000 infant days) were the most common laboratory adverse events. The most common clinical adverse events were medical necrotizing enterocolitis (64/2,500 infants, 3%) and seizure (60/2,500 infants, 2%).Conclusion The overall incidence of adverse events among infants receiving rifampin appears low; however, additional studies to further evaluate safety and dosing of rifampin in this population are needed.
Keywords: rifampin; broad-spectrum antibiotic; infectious disease; neonatal intensive care unit